2018
DOI: 10.1039/c7sc04507g
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of multiblock copolymers via step-wise addition of l-lactide and trimethylene carbonate

Abstract: The synthesis of up to pentablock copolymers from various combinations of l-lactide and trimethylene carbonate was accomplished using a dinuclear zinc complex, and the physical, thermal, and mechanical properties of the resulting copolymers evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 85 publications
(62 reference statements)
2
26
0
Order By: Relevance
“…We previously described the preparation and investigation of the solution state behavior of [(fc P,B )Zn(μ-OCH 2 Ph)] 2 ( Abubekerov et al., 2018 ). Our studies revealed that this compound retains its dimeric state before and during the ring-opening polymerization of LA and TMC.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously described the preparation and investigation of the solution state behavior of [(fc P,B )Zn(μ-OCH 2 Ph)] 2 ( Abubekerov et al., 2018 ). Our studies revealed that this compound retains its dimeric state before and during the ring-opening polymerization of LA and TMC.…”
Section: Resultsmentioning
confidence: 99%
“…However, after the reaction onset, the signals corresponding to (fc P,B )Zn(OPh) do not shift in the 1 H NMR spectra ( Figure S24 ); this finding prompted a further look into the polymerization process by diffusion ordered spectroscopy. We previously used this technique to illustrate that our zinc polymerization systems show the same diffusion rate for the catalyst and the polymer ( Abubekerov et al., 2018 ). However, in the present case, the diffusion rate of polylactide (PLA) was substantially different from that of (fc P,B )Zn(OPh), suggesting that (fc P,B )Zn(OPh) does not participate in the polymerization process ( Figure S26 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is unusual for metal complexes to be able to ring open TMC in the presence of LA, due to a strong 5‐membered ring metal lactide‐coordination‐insertion intermediate, but we attempted to study this reaction further given the success in synthesizing the (PTMC/PLA)‐PCHO‐PLA‐O i Pr block copolymer. First, LA was polymerized to a near full completion, which required heating for 4 days at 100 °C (Table , entry 6).…”
Section: Resultsmentioning
confidence: 99%